A RARE CASE OF DICEPHALIC MONSTER ALONG WITH FETAL ASCITES IN A NON-DESCRIPT CATTLE - YADAV, BRIJESH KUMAR; BASERA, ASHUTOSH; PASHA, ASIF; AGRAWAL, JITENDRA; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2020)
The present communication reports the delivery of a monster fetus by caesarean in a non-descript cattle. The delivered fetus was dicephalic, and with ascites, which is rare.